1999
DOI: 10.1159/000015293
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in pig sperm: multicolor fluorescence in situ hybridization using probes for chromosomes 1, 10, and Y

Abstract: The objective of this research was to develop chromosome-specific probes for use in evaluating aneuploidy in boar spermatozoa through the application of fluorescence in situ hybridization (FISH) technology. A multicolor FISH method was developed to detect aneuploidy in the sperm of boars using DNA probes specific for small regions of chromosomes 1, 10, and Y. The average frequencies of sperm with disomy for chromosomes 1, 10, and Y were 0.075%, 0.067%, and 0.094%, respectively. The incidence of disomy did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
8
36
0
Order By: Relevance
“…Such results have been reported only once before in the pig species, for chromosomes 1, 10 and X [34]. The results obtained in the present study (nullisomy and disomy rates comprised between 0.02% and 0.08%) are close to those reported by Rubes et al [34] for the autosomes (0.075% and 0.067% for chromosomes 1 and 10, respectively). However, these values appeared rather different than those recently obtained in humans (identical disomy rates for all autosomes: 0.24% [32]).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such results have been reported only once before in the pig species, for chromosomes 1, 10 and X [34]. The results obtained in the present study (nullisomy and disomy rates comprised between 0.02% and 0.08%) are close to those reported by Rubes et al [34] for the autosomes (0.075% and 0.067% for chromosomes 1 and 10, respectively). However, these values appeared rather different than those recently obtained in humans (identical disomy rates for all autosomes: 0.24% [32]).…”
Section: Discussionsupporting
confidence: 90%
“…In livestock species, the spermFISH technique was formerly used to quantify X-and Y-bearing sperm in cattle [17,28,31,36] and pigs [23], as well as for the estimation of aneuploidy rates in pigs [34]. We used it for the first time to estimate the proportion of unbalanced gametes in the semen of boars carrying different chromosomal rearrangements, and to predict their effects on reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…No cell was observed to be aneuploid for chromosome Y. These findings were compared with results from our previous studies on aneuploidy in porcine sperm (Rubes et al, 1999) and oocytes (Vozdova et al, 2001). The sum of the frequency of aneuploidy in germ cells from our previous studies is in agreement with the level of chromosome aneuploidy observed in embryos in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Values obtained for embryos are not different from those estimated by extrapolating data from individual germ cells (oocytes and sperms). In previous studies we have determined the frequency of aneuploidy in porcine oocytes (Vozdova et al, 2001) and sperm (Rubes et al, 1999), using the same chromosome-specific probes for chromosomes 1, 10 and Y. A significant difference between aneuploidy of chromosome 1 and 10 was not found in either germ cells or in embryos from pigs.…”
Section: Discussionmentioning
confidence: 99%
“…A Ychromosome-specific probe (Rubes et al, 1999) and a GFP-specific probe (forward, 19-39 nt; reverse, 542-561 nt) were directly labelled with either fluorescein-12-dUTP or tetramethyl-rhodamine-dUTP (Roche) in a PCR reaction. Western blotting.…”
Section: Methodsmentioning
confidence: 99%